Polish Tatars in the Program about Ethnic and National Minorities of Gdansk Pomerania in the Sky Orunia Television - Łyszczarz, Michał (Media - Culture - Social Communication, 2021)
This article is devoted to the problems related to the Polish Tatars, which were presented in a program about ethnic and national minorities in the Sky Orunia television. The author briefly discusses the specificity of the identity of Polish Tatars and the presence of this group in Gdansk Pomerania. He presents the Sky Orunia television, the oldest private local television broadcaster in Poland. Despite the fact that it was a commercial and entertainment broadcaster, it also produced ambitious programs, including a program about national minorities. The Mosaic, produced by Anna Sobecka, was only a short episode in the station history (from February to June 1995, 12 programs were produced). Two episodes of this program were devoted to the Polish Tatars. The first episode presented the history and culture of that minority, while the second episode was dedicated to the cooperation of Polish Tatars with their brothers and sisters from Lithuania and Belarus. In the article, its author used empirical material, which comes from in-depth qualitative interviews with Anna Sobecka.